Direct and indirect effects of leadership styles on employee commitment and performance in Saudi Airlines - Alharbi, Khalid K. (2018)
The Path-Goal Theory is strongly referred to as one of the main organisational subjects of leadership styles in human resources literature. The theory proposes four leadership behaviors that are directive, supportive, participative, and achievement-oriented. In addition, the primary premise of the theory is to predict leadership effectiveness in maximizing employee attitude and performance in different situations. Nevertheless, several deficiencies have been identified in the literature which require further development such as understanding the underlying mechanisms and the boundary conditions of leadership effects. Building on the Path-Goal Theory and the Social Identity Theory, the general objective of this study is to examine the effects of leadership styles on employee affective commitment and performance directly and through the mediating effect of organisational identification, as well as the moderating effect of job security in the context of Saudi Airlines in Saudi Arabia. This is motivated by the fact that Saudi Airlines faces an ongoing internal organisational and external environmental changes, and therefore, the role of organisational identification and job security is relevant. This quantitative study utilized a stratified random sampling technique and used a sample of 353 respondents from the company headquarter, as well as the four international airports of Saudi Arabia (Jeddah, Riyadh, Dammam, and Medina). In addition, the collected data were analyzed using the partial least squares technique to achieve the study findings. In general, these findings revealed that the behaviors of leaders at Saudi Airlines were major determinants of the Path-Goal Theory’s role on subordinates’ attitudes and behavior. It was confirmed that there are significant relationships between leadership styles and the studied outcomes, as well as significant mediating and moderating effects of organisational identification and job security respectively. In specific, the results showed that affective commitment is influenced by participative leadership, achievement-oriented leadership, and organisational identification. Job performance is influenced by supportive leadership, organisational identification, and affective commitment. Organisational identification is influenced by directive, supportive and achievement-oriented leadership. In addition, organisational identification mediates the effect of directive, supportive, and achievement-oriented leadership on affective commitment and job performance. On the other hand, job security had a significant moderating effect on the influence of achievement-oriented leadership style on organisational identification. This study has identified the leadership determinants of organisational identification, affective commitment, and job performance, yet it demonstrates that leadership styles, according to the Path-Goal Theory, are good indicators for employee attitude and performance in the study context.